Uczenie dziecka z traumą. Psychoedukacja. Lekcjoterapia - Rukojć, Katarzyna (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
The growing number of mental disorders among children and teenagers, resulting from fear or distress, but very often also from a traumatic experience, poses yet another challenge a contemporary teacher has to take up. Teaching a child after a traumatic event requires specialistic knowledge and respecting certain rules that provide a guidance in the trauma zone. This article presents basic characteristics of trauma and some dos and don’ts when encountering this phenomenon in the classroom. Additionally, certain therapeutic solutions that can be implemented in the course of the lesson are presented. The article shows that the traumatized children very often have a limited access to psychologists or psychotherapists, therefore they seek help at school where the person they turn to is a teacher, who, despite the lack of professional education in the field of psychology, has tools to offer such children the feeling of safety and the possibility to return to normal functioning or even to post-traumatic growth.